Using Quickbooks Pro 2005 for accounting - Glenn Owen
USING QUICKBOOKS" PRO 2005 FOR ACCOUNTING allows faculty to easily incorporate computerized accounting into the first accounting course. The textbook takes a user perspective by illustrating how accounting information is both used and created. In addition, the text uses proven and successful pedagogy to demonstrate the software's features and elicit student interaction. The text's foremost goal is to help students learn fundamental accounting concepts through the use of QUICKBOOKS" and the analysis of business events. The content complements the first course in accounting and is therefore best used in conjunction with a core text on accounting or after students have had a first accounting course